CODE MIXING AND SWITCHING IN FILM “CRITICAL ELEVEN” BY MONTY TIWA AND ROBERT RONNY - Sintha Yuanita; Sumardi Sumardi (INFERENCE: Journal of English Language Teaching, 2018)
Code mixing and switching in film “Critical Eleven” by Monty Tiwa and Robert Ronny. The objectives of this research are to know the types and the motives of code switching and mixing in the film Critical Eleven. Besides, this research is aimed to know the interferences in the utterances. The theories in this research are proposed by Muysken (2004). This research used descriptive qualitative method. The data of this research was taken from the film transcript. The data is divided into code mixing and code switching. Then, it is analyzed to find the possible reasons of using code mixing and switching. The results of this research are: (1) The most frequent type of code switching was intra-sentential switching that occurred 30 utterances (61,22%). Meanwhile, the most frequent types of code mixing were insertion and alternation. Both types occurred 10 times (47,62%). (2) The most frequent reason of code switching was talking about particular topic (14 data or 28,57%), meanwhile the prestige feeling motive was the most frequent reason of code mixing (18 data or 85,71%). (3) There was an interference in the utterances that is caused by code mixing, but the interference did not occur due to code switching. It happened because the speakers were proficient in Indonesian and English.